Organic acid : an alternative for antibiotic-free feeding in broiler chicken production - S. R. Hasheimi, Zulkifli; Somchit, Muhammad Nazrul; Zakaria, Zunita; Bejo, Mohd Hair; Kok, P. C. (2011)
Antibiotics growth promoters (AGP) have been widely used in intensive animal production. However, there is a concern regarding the possible antibiotic residue effects and the development of antibiotic-resistant population. Organic acids (OA) appear to be potential alternatives to AGP and they have received much attention with OA can reduce pH within the gut and the growth of undesired microorganisms will be suppressed while beneficial bacteria growth is enhanced. The benefits of OA supplementation included improved health and resistance to disease, faster growth, increased feed efficiency and better carcass quality. The improved nutrient digestibility with OA feeding could be associated with its anti-acid-intolerant bacteria such as Escherichia coli, Campylobacter and Salmonella. OA supplementation is beneficial in enhancing the number of Lactobacillus which may reduce colonization of pathogens resistance by competition adhesion for the intestinal epithelium. It is also evident that OA can effectively control Salmonella spp. in poultry.